FROM CYBER DISRUPTION TO DIGITAL TRUST: THE MEDIATING ROLE OF RELIGIOSITY IN ISLAMIC BANKING - Harun Alrasyid; Dinda Dwi Nurrizkiana (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The present study investigates the interplay among trust, perceived security, risk management, and reputation in the context of a cyber-incident in Islamic banking services with religiosity as a mediator. The respondents consisted of 247 Indonesian customers of Islamic banks. PLS-SEM was used to analyze the collected data. The results revealed that religiosity strongly increases the level of trust and mediates the impact of perceived security and reputation. Meanwhile, risk management impacts trust directly. Reputation did not affect the target construct directly, yet had a highly mediated impact on trust through religiosity, suggesting that in a crisis situation, institutional credibility is mainly evaluated through the religious perspective. The present results indicates that the restoration of digital trust in post cyber-incident should be based not only on technical aspects (effective security and risk management) but also on value-based aspects according to the Shariah law. Islamic banks should focus their efforts on communicating cybersecurity measures and practices as part of their ethical responsibility, emphasize accountability and the protection of stakeholders' rights, and work together with religious institutions to build up their credibility. This study contributes to Commitment–Trust Theory, as it reveals that religiosity can be considered an evaluation process in translating institutional practices into trust.